The Empirical Measurement of a Theoretical Concept: Tracing Social Exclusion among Racial Minority and Migrant Groups in Canada - Gingrich, Luann Good (Social Inclusion, 2015)
This paper provides an in-depth description and case application of a conceptual model of social exclusion: aiming to advance existing knowledge on how to conceive of and identify this complex idea, evaluate the methodologies used to measure it, and reconsider what is understood about its social realities toward a meaningful and measurable conception of social inclusion. Drawing on Pierre Bourdieu’s conceptual tools of social fields and systems of capital, our research posits and applies a theoretical framework that permits the measurement of social exclusion as dynamic, social, relational, and material. We begin with a brief review of existing social exclusion research literature, and specifically examine the difficulties and benefits inherent in quantitatively operationalizing a necessarily multifarious theoretical concept. We then introduce our conceptual model of social exclusion and inclusion, which is built on measurable constructs. Using our ongoing program of research as a case study, we briefly present our approach to the quantitative operationalization of social exclusion using secondary data analysis in the Canadian context. Through the development of an Economic Exclusion Index, we demonstrate how our statistical and theoretical analyses evidence intersecting processes of social exclusion which produce consequential gaps and uneven trajectories for migrant individuals and groups compared with Canadian-born, and racial minority groups versus white individuals. To conclude, we consider some methodological implications to advance the empirical measurement of social inclusion.